Conocimiento y factores asociados al consumo de frutas por estudiantes universitarios de la ciudad de Medellín, Colombia (2014)
ABSTRACT: This study aimed to describe habits, preferences, frequency of consumption and knowledge regarding fruit intake among university students in Medellin, Colombia. The sample consisted of 420 randomly chosen male and female students attending both public and private schools with ages ranging from 18-24 years. The sample was selected using a doubly stratified random sampling, with 95% confidence level and 4% maximum permissible error. A multivariate analysis of variance (MANOVA) with canonical contrast of orthogonal type was applied. A statistically significant difference between genders (P<0.05) regarding the opinion on preference and frequency of fruit consumption was found. No difference between socioeconomic level or between attending public and private school (p>0.05) was found. The main conclusion is that university students from Medellin, Colombia, like to eat fruit.